Does the Diagnosis of Breast or Ovarian Cancer Trigger Referral to Genetic Counseling? - Powell, C. Bethan; Littell, Ramey; Hoodfar, Elizabeth; Sinclair, Fiona; Pressman, Alice (International journal of gynecological cancer, 2013)
Kaiser Permanente Northern California is a large integrated health care delivery system in the United States that has guidelines for referring women with newly diagnosed BRCA1-and BRCA2-associated cancers for genetic counseling. This study assesses adherence to genetic counseling referral guidelines within this health system. Chart review was performed to identify patients with cancer who met the following pathology-based Kaiser Permanente Northern California guidelines for referral for genetic counseling: invasive breast cancer, younger than age 40; nonmucinous epithelial ovarian, fallopian tube, or peritoneal cancer, younger than age 60; women with synchronous or metachronous primary cancers of the breast and ovaries; and male breast cancer. We assessed compliance with referral guidelines. An electronic notice was sent to the managing physician of patients with newly diagnosed cancer to assess the feasibility of this intervention. A total of 340 patients were identified with breast cancer at younger than age 40 or with ovarian, peritoneal, or tubal cancer between January and June, 2008. Upon chart review, 105 of these patients met pathology-based criteria for referral to genetic counseling, of whom 47 (45%) were referred within the 2-year study period. Of the 67 subjects with breast cancer, 40 subjects (60%) were referred. In contrast, only 7 (21%) of33 patients with ovarian cancer were referred (P < 0.001). A pilot study was performed to test the feasibility of notifying managing oncologists with an electronic letter alerting them of eligibility for genetic referral of patients with new diagnosis (n = 21). In the 3 to 6 months after this notification, 12 of these 21 patients were referred for counseling including 5 of 7 patients with a diagnosis of ovarian cancer. There is a missed opportunity for referring patients to genetic counseling, especially among patients with ovarian cancer. A pilot study suggests that alerting treating physicians is a feasible strategy to increase appropriate referral.